Home-made Temperature Monitoring System from Four-channel K-Type Thermocouples via Internet of Thing Technology Platform - Detmod, Thitaporn; Ozmen, Yigiter; Songkaitiwong, Kittiphot; Saenyot, Khanuengchat; Locharoenrat, Kitsakorn; Lekchaum, Sarai (AMER INST PHYSICS, 2018)
This paper is aimed to design and construct the home-made temperature monitoring system from four-channel K-type thermocouples in order to improve the temperature measurement based on standard evaluation measurements guidance. The temperature monitoring system was capable to record the temperature on SD card and to display the real-time temperature on Internet of Thing Technology platform. The temperature monitoring system was tested in terms of the temperature measurement accuracy and delay response time. It was found that a standard deviation was acceptable as compared to the Instrument Society of America. The response time of the microcontroller to SD card was 2 sec faster than that of the microcontroller to Thingspeak.
Keywords: Engineering; Materials Science; Physics